An ultralow-power memory-based big-data computing platform by nonvolatile domain-wall nanowire devices - Wang, Yuhao (2013)
As one recently introduced non-volatile memory (NVM) device, domain-wall nanowire (or race-track) has shown potential for main memory storage but also computing capability. In this paper, the domain-wall nanowire is studied for a memory-based computing platform towards ultra-low-power big-data processing. One domain-wall nanowire based logic-in-memory architecture is proposed for big-data processing, where the domain-wall nanowire memory is deployed as main memory for data storage as well as XOR-logic for comparison and addition operations. The domain-wall nanowire based logic-in-memory circuits are evaluated by SPICE-level verifications. Further evaluated by applications of general-purpose SPEC2006 benchmark and also web-searching oriented Phoenix benchmark, the proposed computing platform can exhibit a significant power saving on both main memory and ALU under the similar performance when compared to CMOS based designs.